Dendritic cells and their associated pro-inflammatory cytokines augment to the inflammatory milieu in vitiligo skin. (December 2021) - Singh, Ashu; Das, Dayasagar; Kurra, Santosh; Arava, Sudheer; Gupta, Somesh; Sharma, Alpana
Highlights: Elevated frequency of mDCs and pDCs seen in circulation of generalized vitiligo (GV) patients. Discrepancy in levels of cytokines and expression of CD40 and CD80 detected in GV patients. Infiltration of Langerhans cells observed in lesional area of GV patients. Defective antigen presentation by DCs may contribute in the pathogenesis of GV. Abstract: Background and Aim: Vitiligo is a progressive, autoimmune, hypomelanotic acquired disorder of skin which is characterized by depigmentation. The initial immunological events of this diseases are still at enigma that includes breach of immune tolerance, and defect in antigen presentation. Hence, we aimed to explore role of Dendritic cells (DCs) and its associated cytokines in the pathogenesis of generalized vitiligo (GV) patients. Methodology: For this case-control study, 20 active patients and controls were enrolled. Phenotypic characterization of myeloid and plasmacytoid DCs (mDCs, pDCs) were done by flow-cytometry. Primary culture of DCs was done by monocyte differentiation supplemented with rIL-4 and rGM-CSF. Functional analysis DCs related cytokines and co-stimulatory molecules (CD80, CD40) was done by ELISA and qPCR respectively. Tissue localization of DCs was evaluated by immunohistochemistry. Result: The frequency of mDCs (0.3715% v/s 0.188%) and pDCs (0.2331% v/s 0.1156%) were elevated in patients as compared to controls. Circulatory level of IL-12, TNF-α were significantly higher whereas IFN-α was decreased in patients than controls. Similar results were obtained in the culture supernatants of patients. Relative mRNA expression profiling of co-stimulatory molecules (CD80, CD40) were found to be up regulated in patient's skin. Tissue localization of Langerhans cells (Langerin, CD1a + ) were found to be significantly higher in patients. Conclusion: Elevated frequency of mDCs and pDCs along with elevated levels of IL-12, TNF-α and CD80, CD40 may contribute in defective antigen presentation of DCs. Altered pro-inflammatory and anti-inflammatory cytokines along with tissue localization of Langerhans cells might be involved in the pathogenesis of GV. These DCs associated cytokines can be explored as a therapeutic target in future.